2013
DOI: 10.1371/journal.pone.0073493
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship of Nerve-Highlighting Fluorophores

Abstract: Nerve damage is a major morbidity associated with numerous surgical interventions. Yet, nerve visualization continues to challenge even the most experienced surgeons. A nerve-specific fluorescent contrast agent, especially one with near-infrared (NIR) absorption and emission, would be of immediate benefit to patients and surgeons. Currently, there are only three classes of small molecule organic fluorophores that penetrate the blood nerve barrier and bind to nerve tissue when administered systemically. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 32 publications
(34 reference statements)
1
52
0
Order By: Relevance
“…Fluorescence cannot only be used to mark sites of pathology for resection but also to mark sensitive areas for the surgeon to avoid [5][6][7][8][9]. Increased availability of specific fluorescent probes which delineate ducts, tissues and/or molecular expression will continue, and these will gradually find successful applications in surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence cannot only be used to mark sites of pathology for resection but also to mark sensitive areas for the surgeon to avoid [5][6][7][8][9]. Increased availability of specific fluorescent probes which delineate ducts, tissues and/or molecular expression will continue, and these will gradually find successful applications in surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are currently few clinically approved fluorophores, none of which are nerve specific. 7,13 The oxazine fluorophore scaffold presents a unique chemical scaffold for tissue-specific Fig. 9 In vivo ratiometric tissue-specific staining after direct administration.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] A limited number of small molecule fluorescent contrast agents exist that stain nerve tissue in vivo, with six known classes of small molecule fluorophores that have been shown to have nerve or brain specificity. These include a handful of stilbene derivatives, 10 a coumarin analog, 11 a library of distyrylbenzene derivatives, [12][13][14][15] 8 styryl pyridinium (FM) fluorophores, 16,17 an oxazine fluorophore, 2,18 and a tricarbocyanine fluorophore. 19 Unfortunately, adipose specificity often accompanies nerve specificity for these small molecule fluorophores, 2,13,14 which is largely by necessity since the molecular composition of nerve and adipose tissues is similar, 20,21 making specific accumulation in the nerve without adipose accumulation a substantial challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The affinity for MBP was maintained provided certain structural features were conserved. 22 We have shown that both the absorption and the emission maxima can be red-shifted significantly by employing through-π system conjugated donor-acceptor (D-A) group, producing dyes with large Stokes shifts, thus minimizing the impact of autofluorescence in the visible region.…”
Section: Introductionmentioning
confidence: 99%